Ileocecum within the sac of left incarcerated inguinal hernia complicated by a iliopsoas abscess—report of a case - NAKAMURA, Tomoki; HANASHI, Tomoko; TAKECHI, Masahiko; KONDOH, Yasumasa; ITOH, Eisuke; TANAKA, Yoichi (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2012)
A 76-year-old man developed left inguinal pain and swelling, as well as a gait disorder and a high fever. The scrotum was the size of a volleyball ; repositioning the contents by hand was impossible. A left incarcerated inguinal hernia was diagnosed. A gastrografin enema showed that the contents included the cecum. An iliopsoas abscess seen on computed tomography (CT) was suspected as the cause of the high fever. A hernia repair and the drainage of the abscess was not done at the same time that the illiopsoas abscess was dealt with due to concerns about operation site contamination. Once the patient was under general anesthesia the contents of the hernia were found in the abdominal cavity during surgery. The posterior wall was reinforced using a direct Kugel patch. CT-guided puncture of the iliopsoas abscess was performed two weeks after the hernia operation. The high fever subsided immediately after the CT-guided puncture. To date, there has been no recurrence of the hernia or the high fever.